Pengembangan Bahan Ajar Evaluasi Pembelajaran Berbasis Transdisipliner - Ananda, Rusydi; Rafida, Tien (Fitrah: Journal of Islamic Education, 2023)
Learning success is one of the factors determined by teaching materials, but teaching materials compiled by lecturers are often not in accordance with university policies. In this regard, this study aims to produce learning evaluation teaching materials based on transdisciplinary. The focus of the study is on three things, namely feasibility, practicality, and effectiveness of transdisciplinary based learning evaluation courses. The research method uses research and development with reference to the theory of the Gall, Gall and Borg model which recommends the model developed by Dick, Carey and Carey. The results showed: (1) the transdisciplinary based learning evaluation course was developed starting from needs analysis, design, trial and revision. The developed learning is equipped with lecturer manuals, student manuals, and teaching books, (2) transdisciplinary based evaluation learning has been validated for its feasibility by learning design experts and material experts, with the results showing the learning product is feasible to use, (3) transdisciplinary based evaluation learning developed, has a practicality level with a score of 3.28 in the practical category, (4) transdisciplinary based evaluation learning is proven to be effective in improving student learning outcomes, with an N-Gain Score of 0.38 in the medium effectiveness category.